2012
DOI: 10.1590/s0004-282x2012001100005
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory changes in Parkinson's disease may be unrelated to dopaminergic dysfunction

Abstract: OBJECTIVE: To investigate the maximal inspiratory pressure (MIP) and maximal expiratory pressure (MEP) in patients with Parkinson's disease (PD) during the on and off periods of levodopa and to compare with healthy controls. METHODS: Twenty-six patients were analyzed with Hoehn and Yahr scores (2-3) and 26 age and gender matched-controls. Statistical analysis was performed with Student's t-test for paired and independent samples. RESULTS: MIP and MEP values in patients were significantly lower than the values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 21 publications
1
38
0
5
Order By: Relevance
“…We chose to maintain this delimitation, as previous studies show that medication based on dopamine (for PD) does not exercise any influence on the subjects' parameters of P Imax and P Emax , just like medication based on acetylcholinesterase inhibitors and N-methyl-D-aspartate antagonists (for AD), which have a neuro-psycho-behavioral action. 23,35 Limitations Although we believe this study does have merits, the limitations should be pointed out. One limitation is that we used cross-sectional data that do not allow us to assess causal relationships.…”
Section: Respiratory Strength In Parkinson's and Alzheimer's Diseasementioning
confidence: 92%
See 2 more Smart Citations
“…We chose to maintain this delimitation, as previous studies show that medication based on dopamine (for PD) does not exercise any influence on the subjects' parameters of P Imax and P Emax , just like medication based on acetylcholinesterase inhibitors and N-methyl-D-aspartate antagonists (for AD), which have a neuro-psycho-behavioral action. 23,35 Limitations Although we believe this study does have merits, the limitations should be pointed out. One limitation is that we used cross-sectional data that do not allow us to assess causal relationships.…”
Section: Respiratory Strength In Parkinson's and Alzheimer's Diseasementioning
confidence: 92%
“…23 Mehanna and Jankovic 24 hypothesized that the respiratory dysfunctions in PD may be the result of muscle dystonia causing abnormal rhythmic oscillations in the supraglottic structures. In addition to this, rigidity, freezing, and bradykinesia exacerbate the restrictive pulmonary dynamic, which, associated with the inefficacy of the cough reflex, predisposes the subject to an elevated risk of aspiration pneumonia.…”
Section: Respiratory Strength In Parkinson's and Alzheimer's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the motor deficits patients with PD frequently exhibit non-motor symptoms, which although significant are still often undiagnosed and untreated [3]. Among the latter are respiratory disturbances: restrictive pulmonary function, respiratory dysrhythmias and upper airway dysfunction [4, 5]. Ventilatory response to hypoxia (HVR) has been examined in very few human studies, which showed quite divergent results: enhanced response [6], diminished [7, 8] and unchanged [9].…”
Section: Introductionmentioning
confidence: 99%
“…Credita--se essa melhora à reversão parcial da deficiência motora, resultando em diminuição do tremor e rigidez muscular, melhora na coordenação dos mús-culos e facilitação do movimento. (19) Guedes, (24) ao investigarem a PImáx e a PEmáx no período on e off da medicação, comparando a um grupo controle, encontraram valores menores em ambos os perío-dos, estando essa disfunção respiratória presente independente do estadiamento da doença. Os resultados de outra pesquisa indicaram que apenas indivíduos que apresentavam obstrução das vias aéreas superiores obtiveram resultados significativos após a utilização da levodopa.…”
Section: Discussionunclassified